Microstructure modification of cement pastes using nanosilica - Daniel Ňachaj; Jiří Němeček; Jiří Němeček (Acta Polytechnica CTU Proceedings, 2022)
The paper describes modifications of cement paste mixtures using nanosilica to affect their physical and chemical properties. Cement pastes from Portland cement CEM I 42.5R with three different substitution ratios of nanosilica 1.5, 3 and 4.5 wt.%/cem. were examined. Micromechanical response and microstructure were characterized using nanoindentation, statistical deconvolution and scanning electron microscopy. About 400 locations were examined on each sample over 40,000 μm2 area. The results indicate an increase of C-S-H phases by 11 vol.% in samples with 4.5 wt.% nanosilica replacement compared to pure Portland cement paste. The increase in C-S-H phases volume was accompanied by the decrease in CH phases by approximately 11 vol.%.